The Kābôd of YHWH in the Old Testament: with particular reference to the Book of Ezekiel - Vries, P. de (Studia Semitica Neerlandica, 2016)
The peculiarity of Ezekiel is that kabôd is used almost exclusively as a hypostasis of YHWH. This study highlights the dual and paradoxical nature of the divine kabôd as both defying verbal description and being potentially visible.